Risk of Post-transplant Hepatocellular Carcinoma Recurrence Is Higher in Recipients of Livers From Male Than Female Living Donors. Issue 6 (December 2018) - Han, Sangbin; Yang, Ju Dong; Sinn, Dong Hyun; Kim, Jong Man; Choi, Gyu Sung; Jung, Gangha; Ahn, Joong Hyun; Kim, Seonwoo; Ko, Justin S.; Gwak, Mi Sook; Kwon, Choon Hyuck D.; Leise, Michael D.; et al.
Abstract : Objective: To evaluate the relationship between donor sex and hepatocellular carcinoma (HCC) recurrence after living donor liver transplantation. Background: HCC shows a male predominance in incidence and recurrence after tumor resection due to sex differences in hepatic sex hormone receptors. There have been no studies evaluating the importance of donor sex on post-transplant HCC recurrence. Methods: Of 384 recipients of livers, from living donors, for HCC: 104/120 who received grafts from female donors were matched with 246/264 who received grafts from male donors using propensity score matching, with an unfixed matching ratio based on factors like tumor biology. Survival analysis was performed with death as a competing risk event. The primary outcome was overall HCC recurrence. Results: The median follow-up time was 39 months. Before matching, recurrence probability at 1/2/5 years after transplantation was 6.1/9.7/12.7% in recipients with female donors and 11.7/19.2/25.3% in recipients with male donors. Recurrence risk was significantly higher with male donors in univariable analysis (hazard ratio [HR] = 2.04 [1.15–3.60], P = 0.014) and multivariable analysis (HR=2.10 [1.20–3.67], P = 0.018). In the matched analysis, recurrence risk was also higher with male donors (HR=1.92 [1.05–3.52], P = 0.034): both in intrahepatic recurrence (HR=1.92 [1.05–3.51], P = 0.034) and extrahepatic recurrence (HR=1.93 [1.05–3.52], P = 0.033). Multivariable analysis confirmed the significance of donor sex (HR=2.08 [1.11–3.91], P = 0.023). Interestingly, the significance was lost when donor age was >40 years. Two external cohorts validated the significance of donor sex. Conclusions: Donor sex appears to be an important graft factor modulating HCC recurrence after living donor liver transplantation. Abstract : Supplemental Digital Content is available in the text